Pemanfaatan Larva Black Soldier Fly (BSF) dalam Pengolahan Air Lindi (Leachate) - Naniek Ratni; Ivon Dewinda (Yayasan Literasi Sains Indonesia, 2022)
The impact of landfilling is the emergence of leachate which contains suspended and dissolved solids, organic and inorganic chemicals which are quite high and have the potential to cause environmental pollution. The lack of variety of leachate treatment makes many researchers start looking for effective ways to reduce leachate. One of the methods proposed is to use decomposer organisms, namely Black Soldier Fly (BSF) insects. The purpose of this study was to determine the effectiveness of Black Soldier Fly (BSF) larvae in processing leachate from organic waste from TPS. The research method used growing media or a mixer in the form of chicken feed and variations in leachate concentrations, namely 25%, 40%, 55%, 70%, 85%, and 100% (L25, L40, L55, L70, L85, and L100). The results showed that Black Soldier Fly (BSF) larvae were quite effective in processing leachate for 22 days. The concentration of leachate is quite influential in leachate processing, the greater the concentration, the higher the level of effectiveness. The effectiveness of leachate treatment using BSF larvae is based on the highest media weight loss, namely in the L100 treatment, which is 57.13% and the lowest in the L25 treatment, which is 48.49%.